Novel LncRNA ZFHX4-AS1 as a Potential Prognostic Biomarker That Affects the Immune Microenvironment in Ovarian Cancer - Wang, Xiaoyan; Wang, Yiwen; Sun, Fusheng; Xu, Yang; Zhang, Zhaocong; Yang, Chang; Zhang, Lijie; Lou, Ge (Frontiers in Oncology, 2022)
Background Ovarian cancer (OvCa) is a malignant disease of the female reproductive system with a high mortality rate. LncRNA has been confirmed to play a crucial role in the development and progression of various cancer types. Novel lncRNA ZFHX4-AS1 has been reported in several cancers, albeit its functional mechanisms in OvCa remain unclear. Methods With reference to the public databases and based on integrating bioinformatics analyses, we explored the expression of ZFHX4-AS1 and its roles in the prognosis of OvCa. We employed the Kaplan-Meier curves to investigate the outcome of patients with different ZFHX4-AS1 expressions. Furthermore, its biological function and the related hallmark pathways were assessed through Gene Ontology (GO) annotation, Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses, and Gene-set enrichment analysis (GSEA). We explored the correlation between lncRNA ZFHX4-AS1 and tumor-infiltrating immune cells through CIBERSORT. The immune checkpoints associated with lncRNA ZFHX4-AS1 and its related genes were investigated. The effect of lncRNA ZFHX4-AS1 on proliferation, invasion and migration of OvCa cells was verified through Cell Counting Kit (CCK)-8, colony formation, wound healing and transwell assays. Results The expression of lncRNA ZFHX4-AS1 was upregulated in OvCa relative to that in normal tissues. Increased lncRNA ZFHX4-AS1 expression was associated with poor overall survival and progression-free survival in OvCa. The GO and KEGG pathway analyses revealed the role of lncRNA ZFHX4-AS1 in cell metabolism, protein synthesis, cell proliferation, and cell cycle. GSEA indicated the hallmark gene sets that were significantly enriched in the high and low expression groups. The CIBERSORT database revealed M2 macrophages, memory B-cells, naïve B cells, and activated NK cells were affected by lncRNA ZFHX4-AS1 expression (all P < 0.05). The expression of lncRNA ZFHX4-AS1 and its related differential genes MRPS11, NSA2, and MRPL13 were significantly correlated with the immune checkpoints. Knockdown of lncRNA ZFHX4-AS1 could inhibit the proliferation, invasion and migration of OvCa cells. Conclusions The results suggested that lncRNA ZFHX4-AS1 is a novel prognostic biomarker associated with cell proliferation, metabolism, infiltration, and distribution of tumor-infiltrating immune cells in OvCa, indicating that lncRNA ZFHX4-AS1 can be used as a potential therapeutic target for OvCa in the future.